Revolutionizing respiratory health research: “commercially-available lung-on-a-chip and air-liquid interface systems” - Park, Sohyun; Woo, Chang Gyu; Cho, Young-Jae (Frontiers in Lab on a Chip Technologies, 2024)
Inhalation of ultrafine particles, aerosol contaminants, and cigarette smoke can induce respiratory diseases. As humans are constantly exposed to various exogenous substances, it is crucial to study their impacts on respiratory diseases and airway dysfunction. Recently, organ-on-a-chip technology has been applied in many research studies to understand disease mechanisms, drug screening, and drug testing. The combination of organ-on-a-chip technology and the air-liquid interface (ALI) culture method is emerging as a new platform for realistically mimicking the microenvironment and physiological motions of the human lungs. Breathing motion can be simulated through cyclic stretching, while blood flow can be replicated using channel flow within the chip. The ALI system is critical for mucociliary differentiation, pseudostratified morphology, and epithelial barrier function development. The combination of organ-on-a-chip technology and ALI systems allows the integration of cyclic stretch as a breathing motion and microfluidic channels as circulatory systems. The chip system can also integrate the lung epithelial cells, extracellular matrix, and microstructures, providing microenvironments such as fibroblast, collagen, and immune cells to the epithelial cells. This review discusses chip systems as effective tools for recapitulating human lung environments and how they are applied in biological studies against various pulmonary diseases such as infections or inflammation, fibrosis, and malignancy.